Determinants of Investment Allocations in the Agricultural Sector in Iraq : A Comparison Between the Method of least Squares Approach and the errror Correction Model (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract                 The research aimed to test the relationship between the size of investment allocations in the agricultural sector in Iraq and their determinants using the Ordinary Least Squares (OLS) method compared to the Error Correction Model (ECM) approach. The time series data for the period from 1990 to 2021 was utilized. The analysis showed that the estimates obtained using the ECM were more accurate and significant than those obtained using the OLS method. Johansen's test indicated the presence of a long-term equilibrium relationship between the size of investment allocations and their determinants. The results of the Error Correction Model indicated a positive relationship between the size of investment allocations and the inflation rate, agricultural gross domestic product (GDP) and government revenues. On the other hand, there was a negative and significant relationship between the size of investment allocations and public debt, operational expenses, and investment expenditures in other economic sectors. The research recommends the necessity of balancing the distribution of investment allocations among different economic sectors based on scientific studies and the importance of each sector's impact on economic growth. This includes creating a suitable environment for domestic and foreign private investment, providing infrastructure to stimulate investment, reducing reliance on borrowing to finance public investments, diversifying sources of income.